The comparison between results of disperssion and regression analysis for complete and extreme experiment - Vlastimir, Palić (Journal of Production Engineering, 1984)
This paper compares results of disperssion and regression analysis for two factorial complete and extreme experiment in determining the girder deflection resulted by welding. The application of extreme experiment requires 12 experimental girders insted of 75 experimental girders which are necessary for complete experiment.